2011
DOI: 10.28945/1376
|View full text |Cite
|
Sign up to set email alerts
|

How Do Students View Asynchronous Online Discussions As A Learning Experience?

Abstract: This case study explores students' perceptions of the value of asynchronous online discussions. Postgraduate business students participated in asynchronous online discussions that are part of a blended approach to teaching, learning, and assessment. The students were required to read three refereed journal articles on global human resource information system (HRIS) implementations, write annotated bibliographies, discuss online in groups of four, and reflect on the learning experience. Students' reflections ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…In the online learning environment, ODBs is a collaborative platform that has been designed as an instructional technology tool to address a variety of educational needs (Meyer, 2006;Ruane & Lee, 2016;Zhou, 2015). Research has shown that incorporating technology as an instructional tool clearly influenced students' knowledge, skills, and attitudes in distance education courses (Bassett, 2011;Shana, 2009). In addition, the studies showed that students were satisfied with ODBs as compared to the traditional classroom.…”
Section: Online Discussion Boardsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the online learning environment, ODBs is a collaborative platform that has been designed as an instructional technology tool to address a variety of educational needs (Meyer, 2006;Ruane & Lee, 2016;Zhou, 2015). Research has shown that incorporating technology as an instructional tool clearly influenced students' knowledge, skills, and attitudes in distance education courses (Bassett, 2011;Shana, 2009). In addition, the studies showed that students were satisfied with ODBs as compared to the traditional classroom.…”
Section: Online Discussion Boardsmentioning
confidence: 99%
“…Department of Education, 2009;Waycott, Bennett, Kennedy, Dalgarno, & Gray, 2010) has been conducted to explore the negative and positive factors of using online learning in higher education and the resulting changes in their writing. Other research (Balaji & Chakrabarti, 2010;Bassett, 2011;Du, Zhang, Olinzock, & Adams, 2008;Shana, 2009;Zhang, Goa, Ring, & Zhang, 2007) has examined and explored how students' communication skills, critical thinking skills, and literacy skills and their academic achievements improve overall through ODBs. Some research (Bliss & Lawrence, 2009;Peterson-Karlan, 2011;Kessler, Bikowski, & Boggs, 2012;Lin & Yang, 2011;Ritchie & Black, 2012;Wegmann & McCauley, 2014) has focused on discovering the importance of integrating discussion boards, online chats, and Wikis into the education process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When staff tried to make units more engaging then distance students often lost what they valued most about studying at a distance -namely autonomy and convenience. Bassett (2011), however, found that structuring discussions helped students to participate more effectively and students valued the collaborative experience. Students need to be made aware of their own learning styles as this will help them to identify their strengths and weaknesses and to adapt to the pressures of different learning requirements for their courses (Sadler-Smith & Smith, 2004).…”
Section: Thomasmentioning
confidence: 99%
“…As Brindley et al (2009) suggest, learning should take place in a rich environment that offers opportunity for interaction and connectedness. There are many studies that confirm that interaction among students improves learning and enhances critical thinking in the online environment (Baggaley, 2008;Bassett, 2011;Brindley et al, 2009;Menchaca & Bekele, 2008). Being able to work collaboratively is one of our university's graduate attributes.…”
Section: Thomasmentioning
confidence: 99%
“…Students' online posting and collaboration were meant to support students' face-to-face communication and learning process. In organizing an asynchronous online discussion for students, planning, preparation and structure are of extreme importance (Bassett, 2011). When planning the online discussion, we followed Dillenbourg's (2002) five-stage collaboration script (Table 1).…”
Section: Figure 1: the Design Of The Blended Learning Processmentioning
confidence: 99%